Post Windstorm Evaluation of Critical Aspects Causing Damage to Rural Houses in the Northern Region of Peninsular Malaysia - Shah Zaini, Shaharudin; A. Majid, Taksiah; Che Deraman, Siti Noratikah; Wan Chik, Farah Alwani; Muhammad, Mohd Khairul Azuan (EDP Sciences, 2017)
Rural houses are susceptible to roof blown off and severe damage during a windstorm event due to the lack of engineering considerations. The aim of this paper is to conduct a post windstorm evaluation on the damaged rural houses located in the northern region of Peninsula Malaysia. Several activities were involved during the post windstorm survey including site visualization, site measurement and interview. Critical aspects including types of damages, types of houses, gap height, overhang length, roof geometry, roof pitch, roof cladding and terrain category were analysed using a simple bar chart. It is anticipated that the presence of kitchen house influences the overall stability of the rural houses due to the formation of gap height.